2019
DOI: 10.1002/cam4.2172
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of lung cancer as a second primary malignancy: A population‐based cohort study

Abstract: Lung cancer as a second primary malignancy (lung‐2) is increasingly common, but its prognosis is poorly understood. This study aims to examine the overall and cancer‐specific survival of patients diagnosed with lung‐2 compared to lung‐1. Primary lung cancer patients diagnosed from 1988 to 2014 in the Surveillance, Epidemiology, and End Results (SEER) program were included. Lung‐2 was identified in patients with a previous diagnosis of nonlung primary malignancy in SEER. Hazard ratios (HRs) of overall and lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 17 publications
2
27
0
Order By: Relevance
“…The incidence of previous extrapulmonary malignancies in our study was similar to those reported previously (1-22%) (7,8,(18)(19)(20)(21)(22)(23)(24)(25)(26). Corresponding to an increase in the incidence of multiple primary cancers, a surge of 5.7% in lung cancer as a second primary malignancy was also noted between 1988-1992 and 2011-2014 in the United States National Cancer Institute's Surveillance, Epidemiology, and End Results Program (19).…”
Section: Discussionsupporting
confidence: 89%
“…The incidence of previous extrapulmonary malignancies in our study was similar to those reported previously (1-22%) (7,8,(18)(19)(20)(21)(22)(23)(24)(25)(26). Corresponding to an increase in the incidence of multiple primary cancers, a surge of 5.7% in lung cancer as a second primary malignancy was also noted between 1988-1992 and 2011-2014 in the United States National Cancer Institute's Surveillance, Epidemiology, and End Results Program (19).…”
Section: Discussionsupporting
confidence: 89%
“…Theories to explain this phenomenon including that the majority of AM-GISTs patients diagnosed at an early stage and with a relatively smaller size, as well as more aggressive treatments, may be adopted for GISTs. Moreover, the favorable cancer-specific survival was limited to the first 5 years after diagnosis for those diagnosed as lung cancer after another malignancy, but the survival benefits were somewhat attenuated in the long run [25]. Taken together, we believe that it is still indispensable to increasing surveillance for these patients.…”
Section: Survival Outcomesmentioning
confidence: 86%
“…Theories to explain this phenomenon including that the majority of AM-GISTs patients diagnosed at an early stage and with a relatively smaller size,as well as more aggressive treatments may be adopted for GISTs. Moreover, the favorable cancer-specific survival was limited to the first five years after diagnosis for those diagnosed as lung cancer after another malignancy, but the survival benefits were somewhat attenuated in the long run (25). Taken together, we believe that it is still indispensable to increasing surveillance for these patients.…”
Section: Survival Outcomesmentioning
confidence: 87%